2011
DOI: 10.1021/cm2032459
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Multilayer Assemblies on Materials Surfaces: From Cell Adhesion to Tissue Engineering

Abstract: Controlling the bulk and surface properties of materials is a real challenge for bioengineers working in the fields of biomaterials, tissue engineering and biophysics. The layer-by-layer (LbL) deposition method, introduced 20 years ago, consists in the alternate adsorption of polyelectrolytes that self-organize on the material's surface, leading to the formation of polyelectrolyte multilayer (PEM) films. 1 Because of its simplicity and versatility, the procedure has led to considerable developments of biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
319
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(325 citation statements)
references
References 167 publications
4
319
0
2
Order By: Relevance
“…While a more comprehensive characterization of the multilayer formation process and also the presence of intrinsic cross-linking were shown in a previous paper [22], here we focused primarily on the characterization of surface properties and layer thickness, which are important for the interaction with cells [34]. Therefore WCA, zeta potential and ellipsometry measurements were performed.…”
Section: Physicochemical Characterization Of Polyelectrolyte Multilaymentioning
confidence: 99%
“…While a more comprehensive characterization of the multilayer formation process and also the presence of intrinsic cross-linking were shown in a previous paper [22], here we focused primarily on the characterization of surface properties and layer thickness, which are important for the interaction with cells [34]. Therefore WCA, zeta potential and ellipsometry measurements were performed.…”
Section: Physicochemical Characterization Of Polyelectrolyte Multilaymentioning
confidence: 99%
“…34 The obtained multilayers are widely used as controlled-release drug systems without changing their biological function within the coating. [35][36][37][38] Sukhishvili et al have recently reported a coating with a "self-defense" behavior that promotes the release of different dose of antibiotic in function of the decrease of the pH around the surface due to the presence of bacteria. 39 Here, we report, for the first time, polyelectrolyte multilayers films made of poly-(Llysine) and hyaluroanan-aldehyde (PLL/HA-Ald) derivative, which possess the main advantage to form stable structures through an auto-crosslinking mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…It is powerful technique for the fabrication of polymer-based multilayer films with dimensions from nano to micro, adjusted composition, and tunable cellular response. [5][6][7][8][9][10][11] Control over cellular functions such as adhesion, differentiation, and proliferation, 12-15 along with reservoir properties for a variety of biomolecules such as proteins, growth factors, genes, and drugs 7, 16-20 makes these films an attractive platform for cell-based applications.Despite the evident biological potential to employ the multilayers to recapitulate ECM, 3 the options to tune multilayer biodegradability are mostly limited to multilayer chemical 13,[21][22] that can significantly change multilayer properties. There is also a lack in understanding the mechanism of biomolecule-multilayer interaction that obviously defines biomolecule presentation/release from multilayers to cells and, as a result, cellular response.…”
mentioning
confidence: 99%